2018
DOI: 10.1371/journal.pone.0183229
|View full text |Cite
|
Sign up to set email alerts
|

Identification of functional features of synthetic SINEUPs, antisense lncRNAs that specifically enhance protein translation

Abstract: SINEUPs are antisense long noncoding RNAs, in which an embedded SINE B2 element UP-regulates translation of partially overlapping target sense mRNAs. SINEUPs contain two functional domains. First, the binding domain (BD) is located in the region antisense to the target, providing specific targeting to the overlapping mRNA. Second, the inverted SINE B2 represents the effector domain (ED) and enhances translation. To adapt SINEUP technology to a broader number of targets, we took advantage of a high-throughput, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 50 publications
2
28
1
Order By: Relevance
“…Similar to microRNA (miRNA) engineering approaches, where the aim was to target the translation of multiple genes without burdening the overall protein production capacity of a cell, lncRNAs are no burden on the translational machinery and could be used to control gene transcription of target genes rather than their translation, thus intervening at an even earlier stage. While miRNAs can reduce translation of their target, engineering by lncRNAs could also be used to enhance transcription of individual genes, such as the product gene, an approach that has already been shown to work at the level of mRNA translation using lncRNAs (Takahashi et al, ). Speculatively, and excitingly, one could reach a level of understanding that allows control of entire phenotypes—which are determined by transcriptome patterns—by targeting multiple genes in a pathway without interfering with their genomic sequence or context by introducing lncRNAs designed to manipulate their expression patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to microRNA (miRNA) engineering approaches, where the aim was to target the translation of multiple genes without burdening the overall protein production capacity of a cell, lncRNAs are no burden on the translational machinery and could be used to control gene transcription of target genes rather than their translation, thus intervening at an even earlier stage. While miRNAs can reduce translation of their target, engineering by lncRNAs could also be used to enhance transcription of individual genes, such as the product gene, an approach that has already been shown to work at the level of mRNA translation using lncRNAs (Takahashi et al, ). Speculatively, and excitingly, one could reach a level of understanding that allows control of entire phenotypes—which are determined by transcriptome patterns—by targeting multiple genes in a pathway without interfering with their genomic sequence or context by introducing lncRNAs designed to manipulate their expression patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to microRNA (miRNA) engineering approaches, where the aim was to target the translation of multiple genes without burdening the overall protein production capacity of a cell, lncRNAs are no burden on the translational machinery and could be used to control gene transcription of target genes rather than their translation, thus intervening at an even earlier stage. While miRNAs can reduce translation of their target, engineering by lncRNAs could also be used to enhance transcription of individual genes, such as the product gene, an approach that has already been shown to work at the level of mRNA translation using lncRNAs (Takahashi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the transcriptional orientation of genic lncRNAs can be in sense or antisense compared to the transcriptional orientation of protein-coding genes. Genic antisense lncRNAs are transcribed from the opposite strand of the closest protein-coding gene and can overlap with a 5 head-to-head divergent orientation (SINEUPs [38][39][40][41]) or with 3 tail-to-tail convergent orientation (3 overlapping lncRNAs) ( Figure 2B). An example of intronic lncRNA is COLDAIR which is transcribed from the first intron of the coding gene Flowering Locus C (FLC) [42].…”
Section: Genic Lncrnas: Intronic and Exonicmentioning
confidence: 99%
“…. Recent studies showed that the potential of natural SINEUPs is preserved in synthetic SINEUPs designed to specifically target various endogenous and exogenous genes 14,15 . SINEUPs have two important features: first the "binding domain" (BD) which is generally the 5ʹ end region complementary to the sequence encompassing the primary start codon of a protein-coding mRNA, and second the "effector domain" (ED) as it incorporates an inverted repeat of SINE which is a prerequisite for SINEUP function 14 (Figure 1).…”
mentioning
confidence: 99%
“…The protein induction is maintained within the normal physiological range of the cell, preventing any deleterious effect due to aberrant or excessive protein expression. SINEUPs are compatible with a wide variety of mouse, human, and hamster cultured cell lines, for instance, HEK293T/17, HepG2, HeLa, CHO, MN9D, and many more 12,13,14,15,18,19 . SINEUPs can efficiently target endogenous genes, transiently overexpressed genes, and FLAG-tagged or luciferasefusion genes, eliminating the need of gene-specific antibodies 14,18 .…”
mentioning
confidence: 99%